2017
DOI: 10.1259/bjr.20170512
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric impact of gastrointestinal air column in radiation treatment of pancreatic cancer

Abstract: CBCT revealed large air column in GI structures; however, its impact is minimal for target coverage. Because of the inherent advantage of segmentation in IMRT, where only a small fraction of a given beam passes through the air column, this technique might have an advantage over 3DCRT in treating upper GI malignancies where the daily air column can have significant impact. Advances in knowledge: Radiation treatment of pancreatic cancer has significant challenges due to positioning, imaging of soft tissues and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Multiple studies have found that deviations in delivered dose occur in patients with upper GI cancer who present with varying abdominal gas volumes throughout treatment. 9 , 11 , 13 , 14 However, these studies either fail to report on the treatment technique used, assess intensity modulated radiation therapy, or simply determine their dosimetric differences to be clinically acceptable. The results of the few studies to focus on VMAT treatment delivery 10 , 12 provide support to the findings outlined in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple studies have found that deviations in delivered dose occur in patients with upper GI cancer who present with varying abdominal gas volumes throughout treatment. 9 , 11 , 13 , 14 However, these studies either fail to report on the treatment technique used, assess intensity modulated radiation therapy, or simply determine their dosimetric differences to be clinically acceptable. The results of the few studies to focus on VMAT treatment delivery 10 , 12 provide support to the findings outlined in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Given the low incidence of patients with pancreatic cancer who are prescribed radical radiation therapy and the relatively recent implementation of VMAT as a feasible treatment option, only 8 patients were available to review. This is a common limitation for studies investigating pancreatic cancer, 9 , 10 , 11 , 12 resulting in the inability to assess the true implications of changing gas volumes for VMAT treatment delivery. Greater collaboration between institutions and pooling of data sets may be a viable option to help improve sample size and the quality of results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The abdominal and lower abdominal region is particularly susceptible to daily anatomical variations due to the presence of organs with variable filling, including the gastrointestinal (GI) tract, bowel, bladder, and rectum (Berger et al 2017). GI air volumes were shown to vary by up to ±80% throughout radiotherapy in adult pancreatic cancer patients (Estabrook et al 2018). In children with abdominal cancers, average GI air volume changes of 99.4 ± 126.9 ml (range: 216.7-454.7 ml) have been reported (Guerreiro et al 2019) as well as evidence that younger children under anaesthesia are the most predisposed to variability (Lim et al 2021.…”
Section: Introductionmentioning
confidence: 99%
“…N-board cone-beam computed tomography (CBCT) is widely used in image-guided radiation therapy (IGRT) and shows the potential to aid in adaptive radiation therapy (ART) [1][2][3][4] . Its artifacts, range from those due to inherent limitation of imaging physics, such as scattering, beam hardening, to those caused by the long-time scanning process, such as patient respiratory motion, have been well studied [5][6][7] . Much work has been done on techniques to reduce these artifacts and improve the imaging quality.…”
Section: Introductionmentioning
confidence: 99%